Electrolytic capacitor, and manufacturing method thereof
Patent Information
- Application Number
- JP2024202747
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-04-15
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2042-04-12
AI Technical Summary
【0007】 本発明によれば、電解コンデンサのESRを低減することができる。
Smart Images

Figure 2025024172000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an electrolytic capacitor and a method for manufacturing the same. [Background technology]
[0002] The electrolytic capacitor includes a capacitor element, which includes an anode body, a dielectric layer covering the anode body, and a solid electrolyte layer covering the dielectric layer. The solid electrolyte layer includes a conductive polymer, such as polypyrrole (see, for example, Patent Document 1). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2008-118060 A Summary of the Invention [Problem to be solved by the invention]
[0004] There is a demand for reducing the ESR (equivalent series resistance) of electrolytic capacitors. [Means for solving the problem]
[0005] One aspect of the present invention relates to an electrolytic capacitor including an anode body, a dielectric layer covering the anode body, a first solid electrolyte layer covering the dielectric layer, and a second solid electrolyte layer covering the first solid electrolyte layer, wherein the first solid electrolyte layer includes a first conductive polymer having a polythiophene skeleton and the second solid electrolyte layer includes a second conductive polymer having a polypyrrole skeleton, and the conductivity of the first solid electrolyte layer is 2 S / cm or less.
[0006] Another aspect of the present invention relates to a method for producing an electrolytic capacitor, comprising: a first step of preparing an anode body having a dielectric layer formed thereon; a second step of forming a first solid electrolyte layer on the dielectric layer, the first solid electrolyte layer including a first conductive polymer having a polythiophene skeleton; and a third step of electrolytically polymerizing a precursor of a second conductive polymer having a polypyrrole skeleton on the first solid electrolyte layer to form a second solid electrolyte layer including the second conductive polymer, wherein the first solid electrolyte layer has a conductivity of 2 S / cm or less. Effect of the Invention
[0007] According to the present invention, the ESR of the electrolytic capacitor can be reduced.
[0008] The novel features of the present invention are set forth in the appended claims, but the present invention, both in terms of structure and content, together with other objects and features of the present invention, will be better understood from the following detailed description taken in conjunction with the drawings. [Brief description of the drawings]
[0009] [Figure 1] 1 is a cross-sectional view illustrating a schematic diagram of an electrolytic capacitor according to an embodiment of the present invention. [Diagram 2] FIG. 2 is an enlarged cross-sectional view showing a schematic view of region II in FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] In the following, an embodiment of the electrolytic capacitor according to the present disclosure will be described by way of example, but the present disclosure is not limited to the examples described below. In the following description, specific numerical values and materials may be exemplified, but other numerical values and materials may be applied as long as the effects of the present disclosure are obtained. In this specification, the description "numerical value A to numerical value B" includes numerical value A and numerical value B, and can be read as "numerical value A or more and numerical value B or less." In the following description, when a lower limit and an upper limit of a numerical value related to a specific physical property or condition are exemplified, any of the exemplified lower limits and any of the exemplified upper limits can be arbitrarily combined as long as the lower limit is not equal to or greater than the upper limit. When multiple materials are exemplified, one of them may be selected and used alone, or two or more of them may be used in combination.
[0011] The present disclosure also encompasses any combination of features recited in any two or more claims arbitrarily selected from the multiple claims recited in the accompanying claims, i.e., any combination of features recited in any two or more claims arbitrarily selected from the multiple claims recited in the accompanying claims may be used unless a technical contradiction arises.
[0012] The term "electrolytic capacitor" may be read as a "solid electrolytic capacitor", and the term "capacitor" may be read as a "capacitor".
[0013] An electrolytic capacitor according to an embodiment of the present invention includes an anode body, a dielectric layer covering the anode body, a first solid electrolyte layer covering the dielectric layer, and a second solid electrolyte layer covering the first solid electrolyte layer. The first solid electrolyte layer (hereinafter also referred to as the first layer) contains a first conductive polymer (hereinafter also referred to as a polythiophene-based polymer) having a basic skeleton of polythiophene, and has a conductivity of 2 S / cm or less. The second solid electrolyte layer (hereinafter also referred to as the second layer) contains a second conductive polymer (hereinafter also referred to as a polypyrrole-based polymer) having a basic skeleton of polypyrrole.
[0014] The second layer containing a polypyrrole-based polymer is formed by forming a conductive first layer on a dielectric layer formed on the surface of an anode body, and then electrolytically polymerizing a precursor of the polypyrrole-based polymer on the first layer. The first layer functions as an electrode during electrolytic polymerization. A good second layer is formed by electrolytic polymerization. The present inventors have conducted extensive research on the first layer. As a result, they have newly found that when the first layer contains a polythiophene-based polymer and has a conductivity of 2 S / cm or less, the ESR of an electrolytic capacitor having a second layer containing a polypyrrole-based polymer is reduced.
[0015] When the first layer contains a polythiophene-based polymer and has a conductivity of 2 S / cm or less, an electrolytic capacitor with a second layer containing a polypyrrole-based polymer has a peculiarly low ESR. Although the detailed reason for this is unclear, the following points are presumed to be the factors that lead to the low ESR.
[0016] Crystallization or cracks occurring in a part of the dielectric layer can cause a short circuit, resulting in a high current flow. In such cases, a part of the conductive polymer is usually insulated by the high current, suppressing the short circuit. On the other hand, this insulation increases the resistance of the solid electrolyte layer, raising the ESR.
[0017] In contrast, in the present invention, the conductivity of the first layer is as low as 2 S / cm or less, and it is easy to insulate, and the insulation of the first layer suppresses the insulation of the second layer. In addition, since the first layer is used as an electrode during electrolytic polymerization, it is formed to be sufficiently thinner than the second layer. By locally insulating the first layer, which has a small thickness, the effect of insulation on the entire solid electrolyte layer can be reduced. Therefore, the resistance of the second layer can be maintained low, and an increase in ESR is suppressed.
[0018] It is predicted that the deterioration of the first layer is likely to affect the ESR. However, because the first layer is made of a polythiophene-based polymer film, which has excellent thermal stability and durability, the increase in ESR due to the deterioration of the first layer is suppressed. Furthermore, when the first layer is a polythiophene-based polymer film, the difference in energy level (work function) between the first layer and the polypyrrole-based polymer film (second layer) formed by electrolytic polymerization is smaller than when the first layer is a polypyrrole-based polymer film or a polyaniline-based polymer film formed by chemical polymerization. This is also presumed to be one of the factors behind the low ESR.
[0019] From the viewpoint of reducing the ESR, the electrical conductivity of the first layer is preferably 0.1 S / cm or more and 2 S / cm or less, more preferably 0.1 S / cm or more and 1 S / cm or less, and even more preferably 0.1 S / cm or more and 0.5 S / cm or less. When the electrical conductivity of the first layer is 0.1 S / cm or more, the capacity decrease is easily suppressed.
[0020] The electrical conductivity of the first layer can be determined by the following method. The electrolytic capacitor is disassembled, the capacitor element is taken out, and the components of the first layer are analyzed. When the first layer is formed using a first treatment liquid in the second step described below, the first treatment liquid may be analyzed. Examples of analytical methods that can be used include TEM (transmission electron microscope)-EELS (electron energy loss spectroscopy), NMR (nuclear magnetic resonance spectroscopy), and Raman spectroscopy.
[0021] Based on the analysis results, a sample film (e.g., 20 μm to 40 μm thick) containing the same components as the first layer is formed, and the conductivity of the sample film is determined as the conductivity of the first layer. The sample film can be formed by preparing a sample liquid (aqueous solution) containing the same components as the first layer (e.g., a self-doping polythiophene polymer), applying the sample liquid to a substrate, and drying it. The sample film may be formed using the first treatment liquid. The Loresta-GX and PSP probe manufactured by Nitto Seiko Analytech Co., Ltd. can be used as the conductivity measuring device.
[0022] The first layer has low electrical conductivity. However, by forming the first layer thin, it is possible to suppress an increase in ESR. From the viewpoint of reducing the ESR, the thickness T1 of the first layer is preferably 10 nm or less, and more preferably 5 nm or less. The lower limit of the thickness T1 of the first layer is, for example, 1 nm.
[0023] The thickness T1 of the first layer means the thickness of the first layer covering the inner wall surface of the porous portion of the anode body via the dielectric layer (thickness T1 in FIG. 2). The thickness of the first layer can be determined by the following method. First, the electrolytic capacitor is disassembled to remove the capacitor element, and an image of the cross section of the capacitor element is obtained using a transmission electron microscope (TEM). Using the image, the thickness of any 10 points of the first layer covering the inner wall surface of the porous portion is measured. The average value of the measured thickness values is calculated. The first and second layers can be confirmed by, for example, TEM-EDX (energy dispersive X-ray spectroscopy) analysis (element mapping).
[0024] From the viewpoint of reducing ESR, it is preferable that the second layer has a greater thickness and a higher conductivity than the first layer. From the viewpoint of reducing ESR, the conductivity of the second layer may be 30 S / cm or more, or 60 S / cm or more. From the viewpoint of reducing leakage current, the conductivity of the second layer may be 300 S / cm or less, or 150 S / cm or less. The conductivity of the second layer may be within any range that combines the above upper and lower limits, for example, 30 S / cm or more and 300 S / cm or less, 60 S / cm or more and 300 S / cm or less, or 30 S / cm or more and 150 S / cm or less.
[0025] The thickness T2 of the second layer may be 50 nm or more, or may be 50 nm or more and 100 nm or less. The ratio of the thickness T2 of the second layer to the thickness T1 of the first layer: T2 / T1 may be 10 or more. The thickness T2 of the second layer means the thickness of the second layer (thickness T2 in FIG. 2) covering the outer surface of the porous portion of the anode body via the dielectric layer and the first layer (or the dielectric layer). The thickness of the second layer can be determined by the same method as that for the thickness of the first layer.
[0026] The electrical conductivity of the second layer can be determined by the same method as that of the first layer. Based on the analysis results, a sample film (e.g., 20 μm to 40 μm thick) containing the same components as the second layer is formed, and the electrical conductivity of the sample film is determined as the electrical conductivity of the second layer.
[0027] The second layer is formed by electrolytically polymerizing a precursor of a polypyrrole-based polymer in the presence of a second dopant. Thus, a sample film of the same components as the second layer (polypyrrole-based polymer and second dopant) can be formed by preparing a sample solution containing a precursor of a polypyrrole-based polymer and a second dopant, immersing a metal substrate in the sample solution, passing an electric current through the metal substrate, and electrolytically polymerizing the precursor. In addition, when the second layer is formed using a second treatment liquid in the third step described below, the second treatment liquid may be analyzed, or a sample film may be formed using the second treatment liquid.
[0028] The electrolytic capacitor and the method for manufacturing the same will be described in more detail below. [Electrolytic capacitor] (Anode body) The anode body may contain a valve metal, an alloy containing a valve metal, a compound containing a valve metal, and the like. These materials may be used alone or in combination of two or more. For example, aluminum, tantalum, niobium, and titanium are preferably used as the valve metal. The anode body may have a porous portion on the surface. Such an anode body is obtained, for example, by roughening the surface of a base material (foil-shaped or plate-shaped base material, etc.) containing a valve metal by etching or the like. The anode body may also be a molded body of particles containing a valve metal or a sintered body thereof. Since the sintered body has a porous structure, the entire anode body may be a porous portion.
[0029] (Dielectric layer) The dielectric layer is formed, for example, by subjecting an anode body containing a valve metal to chemical conversion treatment (anodization treatment). The dielectric layer may be formed so as to cover at least a part of the anode body. The dielectric layer is usually formed on the surface of the anode body. The dielectric layer is formed on the surface of the porous part of the anode body, and is formed along the outer surface of the porous part and the inner wall surface of the hole (pit).
[0030] The dielectric layer contains an oxide of the valve metal. For example, when tantalum is used as the valve metal, the dielectric layer contains Ta2O5, and when aluminum is used as the valve metal, the dielectric layer contains Al2O3. However, the dielectric layer is not limited to this and may be any material that functions as a dielectric.
[0031] (solid electrolyte layer) The solid electrolyte layer is formed so as to cover the dielectric layer. The solid electrolyte layer does not necessarily have to cover the entire dielectric layer (entire surface), but may be formed so as to cover at least a part of the dielectric layer. The solid electrolyte layer includes a first layer containing a polythiophene-based polymer, and a second layer containing a polypyrrole-based polymer formed on the first layer. When there is a region on the dielectric layer where the first layer is not formed, the second layer may be formed on the dielectric layer in this region.
[0032] (1st layer) The first layer includes a polythiophene-based polymer. The polythiophene-based polymer includes polythiophene and its derivatives. An example of the polythiophene-based polymer is poly(3,4-ethylenedioxythiophene) (PEDOT).
[0033] From the viewpoint of easiness of impregnation into the pores of the porous portion, the weight average molecular weight of the polythiophene-based polymer may be 100,000 or less, or may be 30,000 or less. The weight average molecular weight of the polythiophene-based polymer is, for example, 1,000 or more. In this specification, the weight average molecular weight is a weight average molecular weight based on polystyrene standard measured by gel permeation chromatography (GPC).
[0034] The first layer may contain a self-doped polythiophene-based polymer having a conductivity of 2 S / cm or less. Particles of the self-doped polythiophene-based polymer tend to become small. Therefore, in this case, it is easy to prepare a dispersion liquid of the polythiophene-based polymer or a solution of the polythiophene-based polymer as the first treatment liquid. Also, it is easy to impregnate the dispersion liquid (solution) of the polythiophene-based polymer into the pores of the porous portion.
[0035] The self-doping type polythiophene polymer refers to a conductive polymer having an anionic group that is directly or indirectly bonded to the polythiophene skeleton of the conductive polymer by a covalent bond. The anionic group of the conductive polymer itself functions as a dopant for the conductive polymer, and is therefore called the self-doping type. The anionic group includes, for example, an acidic group (acid type) or its conjugated anionic group (salt type).
[0036] Examples of the anionic group of the polythiophene-based polymer include a sulfonic acid group, a carboxyl group, a phosphoric acid group, a phosphonic acid group, or a salt thereof (such as a salt with an inorganic base or a salt with an organic base). The polythiophene-based polymer may have one type of anionic group, or may have two or more types of anionic groups. The anionic group is preferably a sulfonic acid group or a salt thereof, or may be a combination of a sulfonic acid group or a salt thereof and an anionic group other than a sulfonic acid group or a salt thereof. The amount of anionic groups contained in the polythiophene-based polymer is preferably 1 to 3, more preferably 1 or 2 (particularly 1), per molecule corresponding to the main skeleton of the polythiophene-based polymer.
[0037] The first layer may include a non-self-doped polythiophene-based polymer and may include a first dopant. The first layer may include a polythiophene-based polymer composite of a polythiophene-based polymer and the first dopant, having a conductivity of 2 S / cm or less. In the first layer, the first dopant may be included in the form of an anion or a salt.
[0038] Examples of non-self-doping polythiophene-based polymers include conductive polymers that do not have anionic groups (specifically, sulfonic acid groups, carboxyl groups, phosphoric acid groups, phosphonic acid groups, and salts thereof) covalently bonded directly or indirectly to the polythiophene backbone of the conductive polymer.
[0039] The first dopant may be, for example, a dopant capable of forming a polyanion. Examples of the first dopant include polyvinyl sulfonic acid, polystyrene sulfonic acid, polyallyl sulfonic acid, polyacrylic sulfonic acid, and polymethacrylic sulfonic acid.
[0040] The first layer may contain a conductive polymer other than a polythiophene-based polymer, but preferably contains a large amount of polythiophene-based polymer. The proportion of polythiophene-based polymer in the total conductive polymer contained in the first layer is, for example, 90% by mass or more, and may be 100% by mass.
[0041] The first layer may be a single layer or may be composed of multiple layers. When the first layer is composed of multiple layers, the polythiophene polymers contained in each layer may be the same or different. The first layer may further contain other components within a range that does not impair the effects of the present invention.
[0042] (2nd layer) The second layer includes a polypyrrole-based polymer. The polypyrrole-based polymer includes polypyrrole and its derivatives. The weight-average molecular weight of the polypyrrole-based polymer is not particularly limited, but is, for example, 1,000 or more and 1,000,000 or less.
[0043] The second layer may contain a non-self-doping polypyrrole-based polymer or a second dopant. Examples of the non-self-doping polypyrrole-based polymer include conductive polymers that do not have anionic groups (specifically, sulfonic acid groups, carboxy groups, phosphoric acid groups, phosphonic acid groups, and salts thereof) that are directly or indirectly covalently bonded to the polypyrrole backbone of the conductive polymer.
[0044] The second dopant may be, for example, a dopant capable of forming an anion. Examples of the second dopant include sulfuric acid, nitric acid, phosphoric acid, boric acid, and organic sulfonic acid. Examples of the organic sulfonic acid include aromatic sulfonic acid. Examples of the aromatic sulfonic acid include benzenesulfonic acid, alkylbenzenesulfonic acid, naphthalenesulfonic acid, and alkylnaphthalenesulfonic acid.
[0045] In the second layer, the second dopant may form a polypyrrole-based polymer complex with the polypyrrole-based polymer. In the second layer, the second dopant may be contained in the form of an anion or a salt.
[0046] The second layer may contain a conductive polymer other than a polypyrrole-based polymer, but preferably contains a large amount of polypyrrole-based polymer. The proportion of polypyrrole-based polymer in the total conductive polymer contained in the second layer is, for example, 90 mass % or more, and may be 100 mass %.
[0047] The second layer may be a single layer or may be composed of multiple layers. When the second layer is composed of multiple layers, the polypyrrole polymers contained in each layer may be the same or different. The second layer may further contain other components within the range that does not impair the effects of the present invention.
[0048] FIG. 1 is a cross-sectional view that shows a schematic structure of an electrolytic capacitor according to an embodiment of the present invention. FIG. 2 is an enlarged cross-sectional view that shows a schematic view of region II in FIG. 1. The electrolytic capacitor 1 includes a capacitor element 2, a resin sealing material (exterior body) 3 that seals the capacitor element 2, and an anode terminal 4 and a cathode terminal 5, at least a part of which is exposed to the outside of the resin sealing material 3. The anode terminal 4 and the cathode terminal 5 can be made of, for example, a metal (copper or a copper alloy, etc.). The resin sealing material 3 has an outer shape of a substantially rectangular parallelepiped, and the electrolytic capacitor 1 also has an outer shape of a substantially rectangular parallelepiped. For example, an epoxy resin can be used as the material for the resin sealing material 3.
[0049] Capacitor element 2 includes an anode body 6, a dielectric layer 7 covering the anode body 6, and a cathode portion 8 covering the dielectric layer 7. Cathode portion 8 includes a solid electrolyte layer 9 covering the dielectric layer 7, and a cathode extraction layer 10 covering the solid electrolyte layer 9. Cathode extraction layer 10 has a carbon layer 11 and a silver paste layer 12.
[0050] The anode body 6 has a porous portion 6a and includes a region facing the cathode portion 8 and a region not facing the cathode portion 8. The porous portion 6a includes a large number of holes P. The holes P may be sponge-like pits or tunnel-like pits. In the region of the anode body 6 not facing the cathode portion 8, an insulating separation layer 13 is formed in a band-like shape on the surface of the anode body 6 adjacent to the cathode portion 8, and contact between the cathode portion 8 and the anode body 6 is restricted. Another part of the region of the anode body 6 not facing the cathode portion 8 is electrically connected to the anode terminal 4 by welding. The cathode terminal 5 is electrically connected to the cathode portion 8 via an adhesive layer 14 formed of a conductive adhesive.
[0051] Principal surfaces 4S and 5S of anode terminal 4 and cathode terminal 5 are exposed from the same surface of resin sealing material 3. These exposed surfaces are used for soldering to a substrate (not shown) on which electrolytic capacitor 1 is to be mounted.
[0052] Carbon layer 11 may be made of any material as long as it is conductive, and may be made of, for example, a conductive carbon material (such as graphite). Silver paste layer 12 may be made of, for example, a composition containing silver powder and a binder resin (such as an epoxy resin). The configuration of cathode extraction layer 10 is not limited thereto, and may be any material as long as it has a current collecting function.
[0053] The solid electrolyte layer 9 is formed so as to cover the dielectric layer 7. The dielectric layer 7 is formed along the surface of the anode body 6 (the outer surface S of the porous portion 6a and the inner wall surfaces of the holes P). The surface of the dielectric layer 7 has an uneven shape formed in accordance with the shape of the surface of the anode body 6. The solid electrolyte layer 9 is preferably formed so as to fill in such unevenness of the dielectric layer 7.
[0054] The solid electrolyte layer 9 includes a first layer 9a and a second layer 9b. The first layer 9a is formed so as to cover the outer surface S of the porous portion 6a and the inner wall surface of the hole P through the dielectric layer 7. The second layer 9b is formed so as to cover the outer surface S of the porous portion 6a through the dielectric layer 7 and the first layer 9a. The second layer 9b is also formed in the hole P of the porous portion 6a, and is formed so as to cover the inner wall surface of the hole P through the dielectric layer 7 and the first layer 9a. The first layer 9a includes a polythiophene-based polymer, and the second layer 9b includes a polypyrrole-based polymer. The conductivity of the first layer 9a is 2 S / cm or less. The first layer 9a and the second layer 9b have thicknesses T1 and T2, respectively.
[0055] The electrolytic capacitor according to the present embodiment is not limited to the electrolytic capacitor having the above structure, and can be applied to electrolytic capacitors having various structures. Specifically, the present invention can be applied to a wound electrolytic capacitor, an electrolytic capacitor using a sintered body of metal powder as an anode body, etc. The anode body may be a porous body in which a part of the anode lead is embedded, and the anode terminal and the anode lead may be electrically connected.
[0056] [Manufacturing method of electrolytic capacitors] A method for producing an electrolytic capacitor according to an embodiment of the present invention includes a first step of preparing an anode body having a dielectric layer formed thereon, a second step of forming a first layer on the dielectric layer, and a third step of forming a second layer on the first layer. The first layer includes a polythiophene-based polymer, and the second layer includes a polypyrrole-based polymer. The first layer has a conductivity of 2 S / cm or less. The second and third steps form a solid electrolyte layer including the first and second layers. The method for producing an electrolytic capacitor may also include a step of preparing an anode body prior to the first step. The method may further include a step of forming a cathode extraction layer and / or a step of sealing the capacitor element. Each step will now be described in more detail.
[0057] (Step of preparing the anode body) In this step, the anode body is formed by a known method depending on the type of the anode body. The anode body can be prepared, for example, by roughening the surface of a foil- or plate-shaped substrate containing a valve metal. By roughening, a porous portion is formed in the surface layer of the anode body. The roughening can be performed by etching the substrate surface (for example, electrolytic etching) as long as the substrate surface can be provided with irregularities.
[0058] Alternatively, a powder of a valve metal (e.g., tantalum) is prepared, and one end of a rod-shaped anode lead in the longitudinal direction is embedded in the powder to obtain a molded body in a desired shape (e.g., block shape).The molded body may be sintered to form an anode body having a porous structure in which one end of the anode lead is embedded.
[0059] (1st step) In the first step, a dielectric layer is formed on the anode body. The dielectric layer is formed by anodizing the anode body. The anodization can be performed by a known method, for example, chemical conversion treatment. The chemical conversion treatment can be performed, for example, by immersing the anode body in a chemical conversion solution to impregnate the surface of the anode body with the chemical conversion solution, and applying a voltage between the anode body as an anode and a cathode immersed in the chemical conversion solution. As the chemical conversion solution, for example, an aqueous solution of phosphoric acid or the like is preferably used.
[0060] (2nd process) The second step may include a step a of preparing a first treatment liquid, and a step b of applying the first treatment liquid to the dielectric layer to form the first layer. In the step b, for example, the anode body on which the dielectric layer has been formed may be immersed in the first treatment liquid and then dried to form the first layer. In the step b, the first treatment liquid may be applied or dropped onto the anode body on which the dielectric layer has been formed, and then dried to form the first layer.
[0061] The first treatment liquid may contain a self-doping polythiophene-based polymer (self-doping type) having a conductivity of 2S / cm or less. In this case, a dispersion containing fine particles of a polythiophene-based polymer or a solution of a polythiophene-based polymer is easily prepared as the first treatment liquid, and the dispersion (solution) of a polythiophene-based polymer is easily impregnated into the pores of the porous portion. The first treatment liquid may also contain a polythiophene-based polymer complex (a complex of a polythiophene-based polymer and a first dopant) having a conductivity of 2S / cm or less. As the polythiophene-based polymer and the first dopant, those exemplified above can be used. The first treatment liquid may further contain other components.
[0062] The first treatment liquid may be, for example, a dispersion (or solution) of a polythiophene-based polymer, or a dispersion (or solution) of a polythiophene-based polymer complex of a polythiophene-based polymer and a first dopant. The first treatment liquid may be obtained, for example, by oxidatively polymerizing a precursor of a polythiophene-based polymer in a dispersion medium (or solvent). Examples of this precursor include a monomer constituting a polythiophene-based polymer, and / or an oligomer in which several monomers are linked together. The first treatment liquid containing a polythiophene-based polymer complex may be obtained by oxidatively polymerizing a precursor of a polythiophene-based polymer in a dispersion medium (or solvent) in the presence of a first dopant.
[0063] The electrical conductivity of the first layer can be adjusted, for example, by the polymerization conditions of the polythiophene-based polymer precursor (for example, the type of polythiophene-based polymer precursor, oxidant, or catalyst), the type of the first dopant, and the like.
[0064] The dispersion medium (or solvent) of the first treatment liquid may be, for example, water, an organic solvent, or a mixture thereof. Examples of the organic solvent include monohydric alcohols (e.g., methanol, ethanol, propanol), polyhydric alcohols (e.g., ethylene glycol, glycerin), and aprotic polar solvents (e.g., N,N-dimethylformamide, dimethylsulfoxide, acetonitrile, acetone, benzonitrile).
[0065] From the viewpoint of easily impregnating the pores of the porous portion with the first treatment liquid, the average particle size of the polythiophene-based polymer (or polythiophene-based polymer composite) particles dispersed in the first treatment liquid may be 100 nm or less, or may be 50 nm or less. The lower limit of the average particle size is not particularly limited, but is, for example, 5 nm or more. The average particle size here means the median diameter (D50) in the volume-based particle size distribution. The average particle size of the polythiophene-based polymer (or polythiophene-based polymer composite) can be obtained, for example, from the particle size distribution by dynamic light scattering (DLS). Specifically, using an aqueous dispersion of particles (first treatment liquid), the particle size distribution of the particles is measured on a volume basis with a dynamic light scattering particle size distribution measuring device (HORIBA, LB-550), and the median diameter (D50) is taken as the average particle size.
[0066] (3rd step) In the third step, a precursor of a polypyrrole-based polymer is electrolytically polymerized on the first layer to form a second layer containing a polypyrrole-based polymer. In the third step, a precursor of a polypyrrole-based polymer (non-self-doped type) may be electrolytically polymerized on the first layer in the presence of a second dopant to form a second layer containing a polypyrrole-based polymer and a second dopant.
[0067] The second layer is formed by electrolytic polymerization using a second treatment liquid. The second layer is formed, for example, by immersing the anode body on which the dielectric layer and the first layer are formed in the second treatment liquid and supplying power from a supply electrode using the first layer as an electrode. The second treatment liquid contains, for example, a precursor of a polypyrrole-based polymer, a second dopant, and a dispersion medium (or solvent).
[0068] Since the first layer has low electrical conductivity, a large overvoltage may occur during electrolytic polymerization. This may affect the formation of the second layer. In order to uniformly form a high-quality second layer on the first layer, which has low electrical conductivity, it is desirable to perform electrolytic polymerization by passing a small current through the first layer.
[0069] The polypyrrole polymer and the second dopant may be those exemplified above. The precursor of the polypyrrole polymer may be, for example, a monomer constituting the polypyrrole polymer, and / or an oligomer in which several monomers are linked together. The dispersion medium (or solvent) may be one exemplified in the first treatment liquid. The second treatment liquid may further contain other components.
[0070] (Step of forming cathode extraction layer) In this step, a cathode extraction layer is formed by sequentially laminating a carbon layer and a silver paste layer on the second solid electrolyte layer formed in step 3. By forming the cathode extraction layer, a capacitor element can be obtained.
[0071] A conductive adhesive layer is disposed on the surface of the cathode extraction layer, and one end of the cathode terminal is electrically connected to the capacitor element via this adhesive layer. As the cathode terminal, any electrode terminal used in electrolytic capacitors can be used without particular limitation, and for example, what is called a lead frame may be used.
[0072] (Process for sealing the capacitor element with resin sealing material) The formed capacitor element is sealed with a resin material together with, for example, a portion of each of the anode terminal and the cathode terminal. This sealing forms a resin sealing material. The resin material is preferably a thermosetting resin (such as an epoxy resin) or a resin composition. The resin sealing material includes a cured product of the thermosetting resin or the resin composition.
[0073] [Example] The present invention will be specifically described below based on examples and comparative examples, but the present invention is not limited to the following examples.
[0074] Examples 1 to 5 and Comparative Examples 1 to 2 (Step of forming a dielectric layer on the surface of the anode body) A tantalum sintered body (porous body) with a part of the anode lead embedded therein was prepared as the anode body. The tantalum sintered body was a rectangular parallelepiped, and the anode lead was planted from one end face of the rectangular parallelepiped. The anode body was anodized in a phosphoric acid aqueous solution to form a dielectric layer containing tantalum oxide (Ta2O5) on the surface of the anode body.
[0075] (Step of forming the first layer) An aqueous dispersion (first treatment liquid) containing a self-doped polythiophene-based polymer having the conductivity shown in Table 1 was prepared as the first conductive polymer (step a). The concentration of the polythiophene-based polymer in the first treatment liquid was 4 mass%. The particles of the polythiophene-based polymer were very small particles (particle diameter less than 1 nm) that were difficult to measure by the DLS method. As the self-doped polythiophene-based polymer, PEDOT having a sulfonic acid group directly bonded to the PEDOT skeleton was used. The anode body on which the dielectric layer was formed was immersed in the first treatment liquid and dried to form the first layer (step b).
[0076] (Step of forming the second layer) An aqueous dispersion (second treatment liquid) containing pyrrole and a dopant (sulfonate having a naphthalene skeleton) was prepared. The concentration of pyrrole in the second treatment liquid can be appropriately selected, for example, in the range of 1 to 6 mass%, and the concentration of the dopant in the second treatment liquid can be appropriately selected, for example, in the range of 3 to 12 mass%.
[0077] The anode body on which the dielectric layer and the first layer were formed was immersed in a second treatment liquid, and electrolytic polymerization of pyrrole was carried out using the first layer as an electrode to form a second layer (conductivity 60 S / cm) containing polypyrrole.
[0078] In this manner, a solid electrolyte layer composed of the first layer and the second layer was formed. The thickness T1 of the first layer was 5 nm. The thickness T2 of the second layer was 100 nm.
[0079] (Step of forming cathode extraction layer) A dispersion liquid in which graphite particles are dispersed in water is applied to the surface of the solid electrolyte layer, and then dried to form a carbon layer. Next, a silver paste containing silver particles and a binder resin (epoxy resin) is applied to the surface of the carbon layer, and then heated to harden the binder resin, thereby forming a silver paste layer. In this manner, a cathode extraction layer composed of a carbon layer and a silver paste layer is formed. In this manner, a capacitor element is obtained.
[0080] (Process for sealing the capacitor element) An anode terminal (anode lead frame) was welded to the anode lead, a cathode terminal (cathode lead frame) was connected to the cathode extraction layer with a conductive adhesive, and the capacitor element was sealed with a resin sealant to produce an electrolytic capacitor.
[0081] In the above-mentioned step of forming the first layer, a self-doping type polythiophene polymer with a different conductivity was used as the first conductive polymer contained in the first treatment liquid, and the conductivity of the first layer was changed to the value shown in Table 1 to fabricate each electrolytic capacitor. In Table 1, A1 to A5 represent the electrolytic capacitors of Examples 1 to 5. B1 and B2 represent the electrolytic capacitors of Comparative Examples 1 and 2.
[0082] Comparative Example 3 In the step of forming the first layer, a first treatment liquid containing a self-doping polyaniline-based polymer (conductivity 0.1 S / cm) was used as the first conductive polymer, and the anode body on which the dielectric layer was formed was immersed in the first treatment liquid and dried to form the first layer containing the polyaniline-based polymer. As the self-doping polyaniline-based polymer, polyaniline having a sulfonic acid group directly bonded to the polyaniline skeleton was used. Except for the above, electrolytic capacitor B3 of Comparative Example 3 was produced in the same manner as in Example 1.
[0083] [evaluation] For the electrolytic capacitors of the examples and comparative examples prepared above, the initial ESR (mΩ) at a frequency of 100 kHz was measured using a four-terminal LCR meter in an environment of 20°C. The capacitance (μF) at a frequency of 120 Hz was also measured. Furthermore, the current flowing through the electrolytic capacitor when held at the rated voltage for 40 seconds was measured, and the current value was calculated as the leakage current. The evaluation results are shown in Table 1.
[0084] In Table 1, the ESR values are shown as relative values with the ESR value of electrolytic capacitor A5 taken as 100. In Table 1, the capacity is taken as 100% and is indicated with a circle if it is 90% or more of the capacity of electrolytic capacitor A5, and an X if it is less than 90% of the capacity of electrolytic capacitor A5. In Table 1, leakage current is indicated with a circle if it is 100 μA or less, and an X if it is greater than 100 μA.
[0085] [Table 1]
[0086] Electrolytic capacitors A1 to A5, in which the conductivity of the first layer containing a polythiophene-based polymer is 2 S / cm or less, exhibited lower ESR and smaller leakage current than electrolytic capacitors B1 to B3. Electrolytic capacitors A2 to A5, in which the conductivity of the first layer containing a polythiophene-based polymer is 0.1 S / cm or more and 2 S / cm or less, exhibited high capacitance along with low ESR.
[0087] In electrolytic capacitors B1 and B2, in which the conductivity of the first layer containing a polythiophene-based polymer is greater than 2 S / cm, the ESR increases and the leakage current also increases. This is thought to be due to the fact that the conductivity of the first layer is greater than 2 S / cm, making it difficult for the first layer to become insulating. In electrolytic capacitor B3, the conductivity of the first layer was 2 S / cm or less, but the ESR increased because a polyaniline-based polymer film was formed as the first layer. [Industrial Applicability]
[0088] The electrolytic capacitor according to the present invention is suitable for use in applications requiring a low ESR.
[0089] Although the present invention has been described with respect to the presently preferred embodiments, such disclosure should not be interpreted as limiting. Various variations and modifications will no doubt become apparent to those skilled in the art to which the present invention pertains upon reading the above disclosure. Accordingly, the appended claims should be interpreted to cover all variations and modifications without departing from the true spirit and scope of the present invention. [Explanation of symbols]
[0090] 1: electrolytic capacitor, 2: capacitor element, 3: resin sealing material, 4: anode terminal, 4S: main surface of anode terminal, 5: cathode terminal, 5S: main surface of cathode terminal, 6: anode body, 7: dielectric layer, 8: cathode part, 9: solid electrolyte layer, 9a: first layer, 9b: second layer, 10: cathode lead layer, 11: carbon layer, 12: silver paste layer, 13: separation layer, 14: adhesive layer
Claims
1. an anode body, a dielectric layer covering the anode body, a first solid electrolyte layer covering the dielectric layer, and a second solid electrolyte layer covering the first solid electrolyte layer, the first solid electrolyte layer includes a first conductive polymer having a self-doped polythiophene as a basic skeleton; the second solid electrolyte layer includes a second conductive polymer having a non-self-doped polypyrrole skeleton; the first solid electrolyte layer does not contain the second conductive polymer or contains the first conductive polymer in a larger amount than the second conductive polymer; the second solid electrolyte layer does not contain the first conductive polymer or contains the second conductive polymer in a larger amount than the first conductive polymer; The thickness of the first solid electrolyte layer is smaller than the thickness of the second solid electrolyte layer, The electrolytic capacitor, wherein the first solid electrolyte layer has a lower electrical conductivity than the second solid electrolyte layer.
2. an anode body, a dielectric layer covering the anode body, a first solid electrolyte layer covering the dielectric layer, and a second solid electrolyte layer covering the first solid electrolyte layer, the first solid electrolyte layer includes a first conductive polymer having a self-doped polythiophene as a basic skeleton; the second solid electrolyte layer includes a second conductive polymer having a non-self-doped polypyrrole skeleton; the first solid electrolyte layer does not contain the second conductive polymer or contains the first conductive polymer in a larger amount than the second conductive polymer; the second solid electrolyte layer does not contain the first conductive polymer or contains the second conductive polymer in a larger amount than the first conductive polymer; The thickness of the first solid electrolyte layer is smaller than the thickness of the second solid electrolyte layer, An electrolytic capacitor, wherein the first conductive polymer has a lower conductivity than the second conductive polymer.
3. The thickness of the first solid electrolyte layer is 10 nm or less, 2. The electrolytic capacitor according to claim 1, wherein the first solid electrolyte layer has a conductivity of 2 S / cm or less.
4. The thickness of the first solid electrolyte layer is 10 nm or less, 3. The electrolytic capacitor according to claim 2, wherein the first conductive polymer has a conductivity of 2 S / cm or less.
5. A first step of preparing an anode body having a dielectric layer formed thereon; a second step of forming a first solid electrolyte layer on the dielectric layer, the first solid electrolyte layer including a first conductive polymer having a self-doped polythiophene as a basic skeleton; and a third step of forming a second solid electrolyte layer on the first solid electrolyte layer, the second solid electrolyte layer including a second conductive polymer having a non-self-doped polypyrrole skeleton, In the second step, the first solid electrolyte layer is formed by a deposition method using a solution or dispersion containing the first conductive polymer; In the third step, the second solid electrolyte layer is formed by electrolytic polymerization using a solution or dispersion containing a precursor monomer or oligomer of the second conductive polymer and a dopant material; The thickness of the first solid electrolyte layer is smaller than the thickness of the second solid electrolyte layer, The method for manufacturing an electrolytic capacitor, wherein the first solid electrolyte layer has a lower electrical conductivity than the second solid electrolyte layer.
6. A first step of preparing an anode body having a dielectric layer formed thereon; a second step of forming a first solid electrolyte layer on the dielectric layer, the first solid electrolyte layer including a first conductive polymer having a self-doped polythiophene as a basic skeleton; and a third step of forming a second solid electrolyte layer on the first solid electrolyte layer, the second solid electrolyte layer including a second conductive polymer having a non-self-doped polypyrrole skeleton, In the second step, the first solid electrolyte layer is formed by a deposition method using a solution or dispersion containing the first conductive polymer; In the third step, the second solid electrolyte layer is formed by electrolytic polymerization using a solution or dispersion containing a precursor monomer or oligomer of the second conductive polymer and a dopant material; The thickness of the first solid electrolyte layer is smaller than the thickness of the second solid electrolyte layer, The method for manufacturing an electrolytic capacitor, wherein the first conductive polymer has a lower conductivity than the second conductive polymer.
7. The thickness of the first solid electrolyte layer is 10 nm or less, 6. The method for producing an electrolytic capacitor according to claim 5, wherein the first solid electrolyte layer has a conductivity of 2 S / cm or less.
8. The thickness of the first solid electrolyte layer is 10 nm or less, The method for producing an electrolytic capacitor according to claim 6 , wherein the first conductive polymer has a conductivity of 2 S / cm or less.
Citation Information
Patent Citations
Solid electrolytic capacitor
JP2011096725A
Solid electrolytic capacitor and method of manufacturing the same
JP2011192688A
Solid electrolytic capacitor
JP2011253878A
Solid electrolytic capacitor
JP2008118060A